The Culture of Power and Governance of Pakistan, 1947-2008 - Ilhan Niaz (Karachi Oxford University Press, 2011)
The Culture of Power and Governance of Pakistan is a provocative and hard hitting explanation of Pakistan's crisis of governance. The explanation combines theoretical insight with declassified historical sources to argue that the crisis of governance has deep roots in the historical experience and elite mentality of the subcontinent.
Include Notes, Bibliography and Index
Keywords: Pakistan -- Politics and government -- Bureaucracy